Parotid Gland Teratoma: An Unusual Tumor in an Uncommon Location - Jain, Himanshi Avinash; Bagri, Puneet Kumar; Tripathy, Amruta; Chaudhary, Kiran (Journal of Orofacial Research, 2025)
Extragonadal Teratomas are seen in 15% of cases and only 3-5% of such cases occur in the head and neck region. However, Teratomas rarely occur in the parotid gland. We present such a case here. A 10-year-old female presented with swelling over the left cheek. After radiological investigations, the patient was planned for surgical excision. Histopathological examination showed a well-encapsulated tumor with cystic and solid components, mainly comprised of mature neural tissue. Foci of glandular tissue and thyroid tissue and extensive areas of mature cartilage were seen. These features were suggestive of mature cystic teratoma of the parotid gland. The patient recovered well postoperatively and now is on follow-up. Due to the rarity of such lesions, it is difficult to diagnose them solely based on radiological investigations. Hence Surgical excision becomes a mainstay of treatment.